“If you wish to see some great theatre…”: Liminality in David Cronenberg’s M. Butterfly - Rybina, Polina (Transcr(é)ation)

(untitled) (Western Libraries, University of Western Ontario, 2024)
David Henry Hwang’s play M. Butterfly (1988), reworked by David Cronenberg into a film (1993), is well-known for its suspension of disbelief (which resulted in some rewriting for the 2017 Broadway revival). While the play and its film adaptation have been extensively discussed in terms of gender and race, performing femininity and masculinity, East and West (Chow, de Lauretis, Levin), I will look at the trope of theatricality in film (Bazin, Sontag, Knopf, Loiselle) and the effects of liminality that it mediates. M. Butterfly ascribes the “betwixt and between,” liminal quality to all complex issues of human existence, including art and politics. The essay illuminates four aspects of the liminal experience: its ability to blur spatial boundaries, to disorient temporarily, to intensify perceptions, and to transform the observers into participants (Turner, Schechner, Fischer-Lichte). M. Butterfly is the story of a French diplomat René Gallimard’s (Jeremy Irons) love for a Peking opera diva Song Liling—a spy and a man in disguise (John Lone). Hwang’s play elaborates on the spatio-temporal aspects of the liminal: the blurred boundaries between the past and the present, the inside and the outside, or the ego versus alter ego. The film places emphasis on the intensifying and transformational potential of the liminal space, relying upon intermedial effects of the theatre within a film. Theatricality flows over into the cinematic reality and creates—through intermedial contact—an alternative reality, self-conscious, disorienting, and hallucinatory. Condensing various liminality effects, the play and its adaptation foster liminal sensibilities in the audiences.